A Three-Phase Interleaved Floating Output Boost Converter - Ajmal Farooq; Zeeshan Malik; Dongchang Qu; Zhaohui Sun; Guozhu Chen (Advances in Materials Science and Engineering)
High step-up dc-dc converter is an essential part in several renewable energy systems. In this paper, a new topology of step-up dc-dc converter based on interleaved structure is proposed. The proposed converter uses three energy storing capacitors to achieve a high voltage gain. Besides the high voltage gain feature, the proposed converter also reduces the voltage stress across the semiconductor switches. This helps in using low rating switching devices which can reduce the overall size and cost of the converter. The operating principle of the proposed converter is discussed in detail and its principle waveforms are analyzed. An experiment is carried out on a 20 V input, 130 V output, and 21 W power prototype of the proposed converter in the laboratory to verify the performance of the proposed converter. An efficiency of 91.3% is achieved at the rated load.